Spiritual strength: taqwa(God conscious) and ihsan - Abdullah, Fatimah (2012)
This paper highlights that Islam, iman and ihsan as three major concepts of the religion of Islam. They are built on each other like tiers, each one logically leading to the next. iman represents the cognitive and belief system, islam the behavioral and practical and ihsan the spiritual pinnacle or the “fruit” of the earlier two steps. Islam contains esoteric and exoteric dimensions. The exoteric aspect concerns matters of practice including practical worshipping and rituals such as performing salat, fasting, paying zakat and hajj and social and moral teachings as manifestation of belief. Beyond and above these external, outward manifestation of religion there is a more profound, subtle and complicated dimension, namely the spiritual dimension of Islam.